THE USE OF THE PROBLEM-BASED LEARNING (PBL) MODEL IN IMPROVING STUDENTS' CRITICAL THINKING SKILLS ON ECONOMY LEARNING SUBJECTS AT SMA NEGERI 2 KARIMUN - Nurul Annisa Deshanty; RR. Sri Kartikowati; Hardisem Syabrus (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper discusses the improvement of students' critical thinking skills through the use of the problem-based learning (PBL) model. The research was conducted at class XI IPS 2 of SMA Negeri 2 Karimun. The approach used is quasi-experimental research with a one-group pretest-posttest design. Data collection techniques used observation sheets and questionnaires. Data on the suitability of the learning process with the model are obtained through observation sheets based on PBL syntax and the level of students' critical thinking skills is obtained through questionnaires of students' critical thinking skills. Data analysis techniques used t-tests. The results indicate that the use of the PBL model can improve students' critical thinking skills. It is evidenced from after implementing the PBL model, the students' critical thinking skills increased from the medium category to the high category with a percentage of 53%. Hence, it is expected for teachers to increase the students' critical thinking skills. Thus, it can be applied through the appropriate learning models, one of which is the problem-based learning model.